Venous thromboembolism in menopausal period – part two - Stefańczyk, Ludomir; Stachowiak, Grzegorz; Grzelak, Piotr; Majos, Agata; Stetkiewicz, Tomasz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2004)
In the first part of this article the aethiology of venous thromboembolism (VTE) has been presented, while its second part deals with some topics concerning VTE imaging diagnostics. The power of: 1) Colour Doppler ultrasonography (USG-CD) in evaluation of lower limbs/pelvis minor venous vessels as well as 2) spiral computed tomography in detecting of pulmonary embolism has been shown. Changes in VTE diagnostics during the latest years are discussed.